Clinical characterization and mutation spectrum of patients with hypertriglyceridemia in a German outpatient clinic - Bardey, Frieda; Rieck, Lorenz; Spira, Dominik; März, Winfried; Binner, Priska; Schwab, Stefanie; Kleber, Marcus E.; Danyel, Magdalena; Barkowski, Rasmus; Bobbert, Thomas; Spranger, Joachim; Steinhagen-Thiessen, Elisabeth; et al. (Journal of lipid research, 2024)
Severe hypertriglyceridemia has predominantly multifactorial causes (MCS). Yet, a small subset of patients have the monogenetic form (FCS). It remains a challenge to distinguish patients clinically, since decompensated MCS might mimic FCS's severity. Aim of the current study was to determine clinical criteria that could sufficiently distinguish both forms as well as to apply the FCS score proposed by Moulin et al. We retrospectively studied 72 patients who presented with severe hypertriglyceridemia in our clinic during a time span of seven years and received genetic testing. We classified genetic variants (ACMG-criteria), followed by genetic categorization into MCS or FCS. Clinical data were gathered from the medical records, and the FCS score was calculated for each patient. Molecular genetic screening revealed eight FCS patients and 64 MCS patients. Altogether, we found 13 pathogenic variants of which four have not been described before. The FCS patients showed a significantly higher median triglyceride level than the MCS patients. The FCS score yielded a sensitivity of 75% and a specificity of 93.7% in our cohort and significantly differentiated between the FCS and MCS group (P < 0.001). In our cohort, we identified several variables that significantly differentiated FCS from MCS. The FCS score performed similar to the original study by Moulin, thereby further validating the discriminatory power of the FCS score in an independent cohort.
Gesehen am 13.05.2025